Examining the Impact of Instagram Engagement and Organizational Transparency on Social Donation Intentions: The Moderating Role of Trust - Yulianti, Elma; Asyari (Universitas Yudharta Pasuruan, 2025)
Introduction: This study investigates the influence of Instagram engagement and organizational transparency on the public's interest in channeling social donations, while also examining the moderating role of trust in these relationships. The research responds to the growing relevance of digital platforms and transparency in encouraging charitable behavior, particularly within local community contexts. Method: The study employed a quantitative approach using primary data collected from 160 respondents in the Tilatang Kamang community, Agam Regency. Data were gathered via a Likert-scale questionnaire distributed through Google Forms. The independent variables were Instagram engagement and Transparency, the dependent variable was Interest in Channeling Social Donations, and Trust served as a moderating variable. Purposive sampling was used, and data analysis was conducted using WarpPLS 7.0. Results: Findings reveal that Instagram significantly and positively affects donation interest (β = 0.69; P = 0.01; R² = 0.47), as does Transparency (β = 0.58; P = 0.01; R² = 0.34). Trust was shown to significantly moderate both relationships: it strengthened the effect of Instagram on donation interest (moderation coefficient = 0.26; R² = 0.22; P = 0.01) and also enhanced the effect of Transparency (moderation coefficient = 0.14; R² = 0.34; P = 0.04). Conclusion: The results suggest that Instagram and transparency are effective drivers of interest in social donations within community settings. Moreover, trust acts as a critical moderating factor that amplifies these effects, highlighting its importance in the design of digital philanthropic strategies.